Characterization of extended-spectrum beta-lactamase-producing escherichia coli isolates from Jurong Lake, Singapore with whole-genome-sequencing - Zhong, Yang (2021)
Background: The fast-spreading of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli (ESBL-producing E. coli) and ESBL genes has become a big challenge to public health. The risk of spreading ESBL genes and pathogens in the environment and community has raised public health concern. The characterizing and whole-genome sequencing studies of ESBL-producing bacteria from reservoir water in Singapore is still limited. Materials and methods: The reservoir water sample was taken from two randomly selected sampling points of the Chinese Garden (Jurong river reservoir), which is a popular reservoir park in Singapore. The bacteria of the water sample were collected with 0.45 µm filter membranes and enriched before processing with ESBL-producing E. coli screening. The collected ESBL positive isolates were further characterized by both phenotypic tests including disc diffusion and microdilution Minimum Inhibitory Concentration (MIC) test, and also genotypic test as whole-genome sequencing analysis. Besides, to investigate the transferability of the resistance gene, a conjugation test was performed with the J53 E. coli strain as the gene receptor. Result: Nine ESBL-producing E. coli isolates were collected and confirmed as ESBL-producing with both phenotypic and genotypic tests. A potential pathogen as ST131 clade A isolate was identified, and all isolates were determined to harbor a blaCTX-M gene. Among them, strain J1E4 was resistant to polymyxin E and confirmed to harboring a conjugatable mcr-1 gene. Further genetic environment analysis has reflected a conversed gene cluster formed by insert sequence (IS), blaCTX-M-15, and WbuC family cupin-fold metalloprotein, which may potentially jump from the plasmids to the chromosome. Conclusion: The first time we reported the whole genome sequencing (WGS) data of ESBL-producing E. coli including potential pathogen (ST131) present in reservoir water in Singapore. The ESBL-producing E. coli from reservoir water also carrying conjugatable colistin resistance genes which may become a risk to human health.